A Novel Tobacco Market Diversification : Unsmoking Rich Countries while Smoking Low-and-Middle Income Countries - Marquez, Patricio V. (World Bank, Washington, DC, 2022)
In this working paper, an exploration of available data and information is conducted and findings presented, to support the view that the dichotomous business model and related harm reduction narrative promoted nowadays by the tobacco industry, merits scrutiny by the international community. The promotion of e-cigarettes as welfare enhancing in rich countries, particularly because they are posited to help adult smokers quit, tends to obfuscate a dire reality. The same tobacco industry that promotes (e-cigarettes as harm reduction in rich countries, derives the bulk of its profits by selling cigarettes in lower income countries.